Come rain or come shine, the species richness will decline in the Moroccan mountains - Cheddadi, Rachid; Kaniewski, David; Marriner, Nick; Bar-Hen, Avner; Hurteau, Matthew D. (Global ecology and conservation, 2024)
Plant species richness in mountainous regions generally follows a unimodal distribution with lower values at both low and high altitudes in relation to precipitation. In the Atlas mountains, Morocco, plant species richness is currently highest at 800–1200 m elevation, but the extent and altitudinal limits of this species-rich belt have shifted in the past with climate change. Here, we trace the evolution of pollen taxonomic richness (PTR) as a proxy for plant species richness, with the aim of understanding the relationship with climatic changes over the past 19,000 years, and make some assumptions about future changes in species richness. Past PTR was inferred through an analogy with an extensive modern pollen dataset, and past climatic variables were reconstructed from a fossil record collected in the Middle Atlas, Morocco. We found that the current PTR distribution in Morocco is more closely associated with precipitation than with temperature. During the last glacial period, both PTR and annual precipitation were low, and the analogs were located at lower altitudes than the altitude of the fossil record. During the early Holocene, the PTR increased by approximately 15%, and the modern analogs were found approximately 600–800 m higher than the analogs of the last glacial period. After 6000 years BP, we observe a steady decline in annual precipitation of approximately 30%, resulting in a species richness loss of approximately 18% and a retreat of the upper boundary of the species-rich belt. Climate projections suggest that annual precipitation in Northwest Africa will decrease by 20–30% over the next 50 years, an annual amount comparable to that of the last glacial period, but under much warmer conditions and in a significantly shorter time. Such a decline in precipitation could result in an unprecedented loss of plant species richness of approximately 15% in just a few decades and put 35% of the protected areas at risk. The forested mountains above 1600 m could then resemble the treeless and less diverse steppes found at higher altitudes above today's tree line.